The dynamic nature of patient engagement within a Canadian patient‐oriented kidney health research network: Perspectives of researchers and patient partners. (27th January 2023) - Elliott, Meghan J.; McCarron, Tamara L.; Schick‐Makaroff, Kara; Getchell, Leah; Manns, Braden; Fernandez, Nicolas
Abstract: Introduction: Canadians Seeking Solutions and Innovations to Overcome Chronic Kidney Disease (Can‐SOLVE CKD) is a pan‐Canadian health research network that engages patients as partners across 18 unique projects and core infrastructure. In this qualitative study, we explored how research teams integrated patient partners into network research activities to inform our patient engagement approach. Methods: To capture a breadth of perspectives, this qualitative descriptive study purposively sampled researchers and patient partners across 18 network research teams. We conducted 4 focus groups (2 patients and 2 researchers; n = 26) and 28 individual telephone interviews ( n = 12 patient partners; n = 16 researchers). Transcripts were coded in duplicate, and themes were developed through an inductive, thematic analysis approach. Results: We included 24 patient partners and 24 researchers from 17 of the 18 projects and all core committees within the network. Overarching concepts relate participants' initial impressions and uncertainty about patient engagement to an evolving appreciation of its value, impact and sustainability. We identified four themes with subthemes that characterized the dynamic nature of patient engagement and how participants integrated patients across network initiatives: (1) Reinforcing a shared purpose ( learning together, collective commitment, evolving attitudes ); (2) Fostering a culture of responsive and innovative research ( accessible supports, strengthened process and product ); (3) Aligning priorities, goals and needs ( amenability to patient involvement, mutually productive relationships, harmonizing expectations ); (4) Building a path to sustainability ( value creation, capacity building, sustaining knowledge use ). Conclusions: Our findings demonstrate the dynamic and adaptive processes related to patient engagement within a national, patient‐oriented kidney health research network. Optimization of support structures and capacity are key factors to promote sustainability of engagement processes within and beyond the network. Patient or Public Contribution: This project was conceived in collaboration with a Can‐SOLVE CKD patient partner (N. F.), with lived experience of kidney failure. He also co‐designed the study′s protocol, led focus groups and researcher interviews, and contributed to data analysis. L. G. has lived experience as a caregiver for a person with CKD and facilitated patient partner focus groups. The patient partners, both of whom are listed authors, provided important insights that shaped our interpretation and presentation of study findings.